2014
DOI: 10.1088/0022-3727/47/28/285401
|View full text |Cite
|
Sign up to set email alerts
|

Tracking plasma generated H2O2from gas into liquid phase and revealing its dominant impact on human skin cells

Abstract: The pathway of the biologically active molecule hydrogen peroxide (H 2 O 2 ) from the plasma generation in the gas phase by an atmospheric pressure argon plasma jet, to its transition into the liquid phase and finally to its inhibiting effect on human skin cells is investigated for different feed gas humidity settings. Gas phase diagnostics like Fourier transformed infrared spectroscopy and laser induced fluorescence spectroscopy on hydroxyl radicals ( • OH) are combined with liquid analytics such as chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
184
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(202 citation statements)
references
References 53 publications
13
184
1
Order By: Relevance
“…monocytes produce reactive species themselves (54). Moreover, the distribution of genes depicted in Venn diagrams clearly shows that the incubation time of plasma is much more important than the treatment time between 20 and 180 s. This finding supports the assumption that plasma-generated stable species in liquids induce the cellular response (55). Additionally, plasma-activated reactions were obtained up to several hours after plasma treatment in post-treatment kinetic measurements (56).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…monocytes produce reactive species themselves (54). Moreover, the distribution of genes depicted in Venn diagrams clearly shows that the incubation time of plasma is much more important than the treatment time between 20 and 180 s. This finding supports the assumption that plasma-generated stable species in liquids induce the cellular response (55). Additionally, plasma-activated reactions were obtained up to several hours after plasma treatment in post-treatment kinetic measurements (56).…”
Section: Discussionsupporting
confidence: 71%
“…We concluded that only concentration-dependent differences were detected. Nevertheless, slight differences between reactions with plasma and those with H 2 O 2 in regard to KEAP1 expression are consistent with the fact that many other compounds (secondary radicals) in plasma interact with cells and provoke differences in their gene and protein expression (46,47,55).…”
Section: Discussionsupporting
confidence: 62%
“…The important role of this effect was determined in a previous study for the same plasma source investigated here. 32 In this study, it was shown that plasma generated…”
Section: Hydrogen Peroxide Generationmentioning
confidence: 88%
“…Changing the composition of the curtain gas strongly influences the reactive component composition generated by the plasma. For instance, humidity variation controls the output of H 2 O 2 and OH [36]. The plasma jet is introduced into the cavity via a side opening.…”
Section: Plasma Jetmentioning
confidence: 99%